THERMAL POWER PLANT BASED ON A FREE PISTON ENGINE AND A RECIPROCATING GENERATOR - Kaluzhsky, D.L.; Mekhtiyev, A.D.; Neshina, Y.G.; Alkina, A.D.; Sarsikeyev, Y.Z. (KU Publ., 2022)
The article discusses an autonomous power supply system based on a Stirling engine and a reciprocating generator. There are analyzed the conditions of its operation, the choice of an external combustion engine and a linear synchronous generator. In the course of solving the problem of supplying autonomous consumers with thermal and electric energy remote from the city infrastructure, a power plant with the capacity of up to 100 VA was developed and manufactured. Its experimental study, as well as the analysis of the patent-information array, made it possible to determine the boundaries of using this technical object. The reciprocating generator is driven by a free-piston engine with an external heat supply. For carrying out field experiments, a prototype laboratory model of a free-piston engine with an external heat supply with a linear alternator has been developed. Its main difference from the known types of Stirling engines is the absence of a massive flywheel with a crankshaft and a crank mechanism, which makes it possible to achieve greater tightness and significantly increases the power on output shaft while limiting the outer dimensions. Air is used as the working medium with addition of a small percentage of water, which makes it possible to develop pressure up to 10 MPa. The technical calculation of the generator design has been given, the force required to develop the needed power during the movable element reciprocating movement has been determined. Solutions have been adopted to suppress acoustic noise causing discomfort to consumers. This can in particular be done by placing vibration dampers and designing a generator with a high efficiency. The design of the moving element should minimize mechanical stress on the windings or magnets. The proposed generator can be competitive and can successfully replace traditional low-power sources of electricity with diesel or gasoline engines.
Keywords: micro power plant; Stirling engine; reciprocating generator; alternative source